Growth environment and organ specific variation in in-vitro cytoprotective activities of Picea mariana in PC12 cells exposed to glucose toxicity: a plant used for treatment of diabetes symptoms by the Cree of Eeyou Istchee (Quebec, Canada) - Ashleigh D. Downing; Hoda M. Eid; Andrew Tang; Fida Ahmed; Cory S. Harris; Pierre S. Haddad; Timothy Johns; John T. Arnason; Steffany A. L. Bennett; Alain Cuerrier (BMC, 2019)
Abstract Background The Cree of Eeyou Istchee (James Bay area of northern Quebec) suffer from a high rate of diabetes and its complications partly due to the introduction of the western lifestyle within their culture. As part of a search for alternative medicine based on traditional practice, this project evaluates the biological activity of Picea mariana (Mill.) Britton, Sterns & Poggenb. needle, bark, and cone, in preventing glucose toxicity to PC12-AC cells in vitro (a diabetic neurophathy model) and whether habitat and growth environment influence this activity. Methods Three different organs (needle, bark, and cone) of P. mariana were collected at different geographical locations and ecological conditions and their 80% ethanolic extracts were prepared. Extracts were then tested for their ability to protect PC12-AC cells from hyperglycaemic challenge at physiologically relevant concentrations of 0.25, 0.5, 1.0 and 2.0 μg/mL. Folin-Ciocalteu method was used to determine the total phenolic content of P. mariana extracts. Results All extracts were well-tolerated in vitro exhibiting LD50 of 25 μg/mL or higher. Extracts from all tested organs showed a cytoprotective concentration-dependent response. Furthermore, the cytoprotective activity was habitat- and growth environment-dependent with plants grown in bog or forest habitats in coastal or inland environments exhibiting different cytoprotective efficacies. These differences in activity correlated with total phenolic content but not with antioxidant activity. In addition, this paper provides the first complete Ultra-Performance Liquid Chromatography-quadrupole time-of-flight (UPLC-QTOF) mass spectrometry analysis of Picea mariana's bark, needles and cones. Conclusions Together, these results provide further understanding of the cytoprotective activity of Canadian boreal forest plants identified by the Cree healers of Eeyou Istchee in a cell model of diabetic neuropathy. Their activity is relevant to diabetic peripheral neuropathic complications and shows that their properties can be optimized by harvesting in optimal growth environments.